Safeguarding the Digital Hearth: A Narrative Inquiry into Muhammadiyah’s Family Education and Resilience Frameworks - Munawir Pasaribu; Rahmadi Ali; Mahmud Yunus Daulay; Nor ‘Adha Ab Hamid (International Journal of Educational Narratives, 2026)
Background Family well-being is a foundational factor in shaping individual character and contributes to broader social resilience. Amid the disruptions of the digital era, families increasingly face risks of disintegration. Muhammadiyah, as a progressive Islamic movement, responds to this challenge through its “Sakinah Family” concept. Purpose This study examines Muhammadiyah’s strategies for building family resilience through da’wah, education, and economic empowerment, and identifies the indicators used to evaluate the effectiveness of these strategies. Method This study employs a descriptive qualitative approach using a literature review. Primary sources include Muhammadiyah’s official documents the Collection of Tarjih Decisions, the Guidelines for Islamic Living for Muhammadiyah Members, and the Guidelines for Married Life supplemented by ‘Aisyiyah’s program reports and prior academic studies. Data were analyzed thematically to identify recurring strategic patterns and their documented outcomes. Results Muhammadiyah disseminates progressive Islamic values through structured study programs at branch, regional, and central levels. ‘Aisyiyah implements this through the “Bina Keluarga Sakinah” program, family counseling, and community-based economic empowerment. Program reports indicate lower self-reported rates of divorce and domestic violence among participating families compared to non-participating members, based on qualitative case documentation rather than controlled quantitative measurement. Conclusion Muhammadiyah’s institutional guidelines and structured programs offer a faith-based model for strengthening family resilience, with documented (though not yet rigorously quantified) positive outcomes. This model demonstrates how religious organizations can meaningfully contribute to national family resilience, while highlighting the need for future quantitative research to validate these preliminary findings.